Population Pharmacokinetics of Ropeginterferon Alfa-2b: A Comparison Between Healthy Caucasian and Chinese Subjects - Min Zhu; Min Zhu; Mei-xia Wang; Zi-ran Li; Zi-ran Li; Wei Wang; Xia Su; Zheng Jiao (Frontiers Media S.A., 2021)
Objective: To develop a population pharmacokinetic (PK) model for ropeginterferon alfa-2b and to compare its PK properties between Caucasian and Chinese populations.Methods: A population PK model was developed based on data from two phase I clinical trials conducted in Caucasian and Chinese individuals, to evaluate the influence of ethnicity on the PKs of ropeginterferon alfa-2b.Results: We included 456 observations from 30 healthy Caucasian subjects and 438 observations from 27 healthy Chinese subjects in the population PK analysis. The PKs of ropeginterferon alfa-2b were best described by a one-compartment quasi-equilibrium approximated target-mediated drug disposition model with first-order absorption and absorption lag times. The typical value (relative standard error%) of apparent clearance (CL/F) and volume of distribution of ropeginterferon alfa-2b in 70-kg subjects were 0.778 (12%) L/day and 2.32 (14%) L, respectively. Body weight was the only significant factor affecting the CL/F. There were no obvious differences in the PK properties of ropeginterferon alfa-2b, and predicted steady-state exposure was similar in the Chinese and Caucasian populations.Conclusion: No significant ethnic differences in ropeginterferon alfa-2b PKs were observed between the Chinese and Caucasian populations.